Clinical Outcomes of Delayed Clearance of Serum HBsAg in Patients with Chronic HBV Infection - Nam, Soon Woo; Jung, Jeong Jo; Bae, Si Hyun; Choi, Jong Young; Yoon, Seung Kew; Cho, Se Hyun; Han, Joon Yeol; Han, Nam Ik; Yang, Jin Mo; Lee, Young Suk (The Korean journal of internal medicine, 2007)
Spontaneous delayed clearance of hepatitis B surface antigen (HBsAg) in patients with chronic HBV infection is a rare event. The aim of this study was to investigate the incidence of delayed clearance of serum HBsAg in chronic HBV infection and to determine the characteristics and clinical outcomes of HBsAg delayed clearance in Korean patients. From April 1981 to June 2003, 4,061 patients who were positive for HBsAg were evaluated retrospectively. The following assessments were undertaken in 47 patients who had spontaneous delayed clearance: liver biochemistry, viral markers, alpha-fetoprotein levels, and radiographic examinations including ultrasonography every three to six months for 6-264 months (median 87.9 months). Twenty-four of 47 patients were asymptomatic carriers. The others included seven patients with chronic hepatitis, seven with liver cirrhosis and nine with hepatocellular carcinoma. The estimated annual incidence of HBsAg seroclearance was 0.4%. The time span from positive HBsAg to HBsAg seroclearance in the AHC, CH, LC, and HCC was 62.9, 141, 63, and 95.3 months during follow up. Twenty-four of 24 AHC remained normal, 5 of 7 CH remained as CH and 2 patients remained normal, 1 of 7 with LC developed HCC and 6 of the LC remained as LC, and 4 of 9 HCC patients died. The clinical course following delayed clearance of HBsAg had diverse outcomes from AHC to HCC. Therefore, these patients require close follow up for the possible development of hepatocellular carcinoma following HBsAg clearance.